A new species of Chrysobothris Eschscholtz, 1829, the first from Fiji (Coleoptera: Buprestidae) - Bellamy, C. L. (Zootaxa, 2009)
The genus Chrysobothris Eschscholtz is one of the oldest buprestid genus-group names (Eschscholtz 1829), one of the largest buprestid genera (706 species, 36 subspecies vide Bellamy 2008:1587–1696) and one of only two truly cosmopolitan buprestid genera (Agrilus Curtis, 1815 being the other). Until recently, species of Chrysobothris were unknown in remote Pacific islands (see Comments below). The addition of this taxon to the list of Fiji Buprestidae increases the total to 50 species and one subspecies in 14 genera, which is certainly a respectably-sized fauna for such a small and remote group of islands.